2008
DOI: 10.2174/156802608784911581
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors in Cancer Therapy: New Compounds and Clinical Update of Benzamide-Type Agents

Abstract: Histone deacetylase (HDAC) inhibitors constitute a novel and growing class of anticancer agents that function by altering intracellular patterns of histone acetylation, the so-called epigenetic "histone code," thereby producing changes in cell cycle arrest, differentiation, and/or apoptosis in tumor cells. This overview describes the chemistry and preliminary characterization of recently disclosed molecules in three major classes of HDAC inhibitors: hydroxamic acids, 2-amino- benzanilides, and cyclic peptides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 70 publications
0
34
0
Order By: Relevance
“…Recently, we reported that the synovial sarcoma-associated SS18-SSX fusion oncoprotein dominantly inhibits EGR1 transcription through polycombmediated chromatin remodeling (Lubieniecka et al, 2008). It is noteworthy that HDAC inhibitors, a new class of anticancer drugs (Moradei et al, 2008;Stimson et al, 2009), can reverse this process. In this study, we show that EGR1 reactivation by HDAC inhibitors has a causal function in the induction of synovial sarcoma cell death by these compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported that the synovial sarcoma-associated SS18-SSX fusion oncoprotein dominantly inhibits EGR1 transcription through polycombmediated chromatin remodeling (Lubieniecka et al, 2008). It is noteworthy that HDAC inhibitors, a new class of anticancer drugs (Moradei et al, 2008;Stimson et al, 2009), can reverse this process. In this study, we show that EGR1 reactivation by HDAC inhibitors has a causal function in the induction of synovial sarcoma cell death by these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several HDAC inhibitors, such as FK228 (also known as romidepsin and depsipeptide), MS-275, SAHA and PXD101, are being tested in clinical trials (Moradei et al, 2008;Stimson et al, 2009), and SAHA has recently been approved for use in T-cell lymphomas (Khan and La Thangue, 2008). At the molecular and cellular levels, it is widely accepted that HDAC inhibitors suppress tumor growth by inducing cyclindependent kinase inhibitor p21/WAF1/CIP1-mediated cell cycle arrest, as well as mitochondrial/cytochrome C-dependent apoptotic cell death (Medina et al, 1997;Archer et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…2,13 These findings led to the development of novel chemotherapeutic drugs including DNTM and HDAC inhibitors that are currently in clinical trials for the treatment of various cancer types. 77,78 Further analyses of normal epigenetic regulatory mechanisms and their aberrancies in cancer may lead to the discovery of new strategies for cancer diagnosis and treatment. differentiation states (e.g., comparing undifferentiated ESCs to cancer cells with a more differentiated phenotype) and not directly linked to malignancy, we analyzed if cell type-specific methylated or expressed genes are enriched for PRC targets.…”
Section: Abnormalities Of Epigenetic Patterns In Cancermentioning
confidence: 99%
“…25,26 To better understand the structureactivity relationship (SAR) and discover novel HDACs inhibitors with high potency and good safety profiles, we embarked on exploration of both the surface-recognition domain and the zinc binding group and on design and synthesis of N-(aminopyridine) benzamide analogues. We report here the SARs, the anti-proliferative activity and the in vivo efficacy of newly synthesized HDAC inhibitors.…”
Section: -20mentioning
confidence: 99%